(3fXGe GdeYdheGJ GdJShjbjIs - (3YHO GdfGUQ(B, (3NQjs ((3GdLRGFQ(B:s (3OGQ GdNdOhfjI(B,s, 2011)
-(3eHGOF heaGgje fXe GdeYdheGJ(B-(3eGgjI fXGe GdeYdheGJ GdJShjbjI(B-(3HfjI hechfGJ fXGe GdeYdheGJ GdJShjbjI(B-(3GdeYdheGJ GdJShbjI heUGOQ GdHjGfGJs
Keywords: (3GdJShjbs; (3GdeYdheGJs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s